(untitled) (Revista Brasileira Multidisciplinar, 2019)
The purpose of this literature review is to discuss the pre-clinical work that evaluated the effect of bisphosphonates on tooth movement induced by orthodontic treatment. A search of articles in Pubmed and Scopus of pre-clinical articles between January 1990 and December 2016 was performed. The following keyword combinations were searched for articles: "alendronate" and "orthodontic"; "Bisphosphonates" and "orthodontic movement"; "Bisphosphonates" and "orthodontic treatment" and "alendronate" and "orthodontic movement" and 57 articles were detected. After the abstracts and titles were read, 16 articles were selected for the complete reading of the texts. It can be concluded that in the animal model the use of bisphosphonates reduces orthodontic movement, which can mean an increase in treatment time.